The RADARSAT-1 Antarctic Mapping Project - Jezek, Kenneth C. (2008)
The University Archives has determined that this item is of continuing value to OSU's history. This report summarizes the motivation, processing procedures and products that were part of the RADARSAT-1 Antarctic Mapping Project (RAMP). RAMP was a collaboration between NASA and the Canadian Space Agency to map Antarctica using the RADARSAT -1 Synthetic Aperture Radar. The project proceeded in two parts. The first part, called Antarctic Mapping Mission -1 that acquired data in 1997, resulted in the first high-resolution radar map of Antarctica. The second part, called the Modified Antarctic Mapping Mission which occurred in 2000, remapped the continent below 80 degrees South latitude and exploited interferometric repeat-pass observations to estimate glacier surface velocities. RAMP project goals and objectives are reviewed here along with several science highlights. These highlights include observations of ice sheet margin change using both RAMP and historical data sets, the discovery of large ice streams in Coates Land, observations of the ice sheet surface-velocity field and changes in the velocity field, and observations of surface change using radar coherence. RAMP data products are summarized and a tabulated list of data products is appended to this report. The appendix also lists all of the partner organizations, including the Alaska Satellite Facility (ASF) DAAC, who have received a copy of the complete data set. NASA Pathfinder Program NASA Polar Oceans and Ice Sheets Program Office of Polar Programs, National Science Foundation Canadian Space Agency